Manufacture Potassium Silicate Fertilizer Based on Quartz Sand from Bangka - Hartono, Arief; Nugroho, Budi; Edwar, Feabri Kurniawan (Jurnal Ilmu Tanah dan Lingkungan, 2023)
One of the efforts to utilize the potential for quartz sand (SiO2) is through the manufacture of potassium silicate (K2SiO3) fertilizer, by reacting SiO2 in quartz sand with potassium hydroxide (KOH).  This study aimed to obtain the optimal temperature in the manufacture of K2SiO3 fertilizer by mixing quartz sand from Bangka with KOH.  Furthermore, the study aimed to evaluate the solubility of fertilizer in the soil and its effect on soil pH, exchangeable aluminum (exchangeable Al), exchangeable potassium (exchangeable K), and available silica (Si) through incubation experiment on Ultisol Darmaga. The results showed that the highest K content in the form of potassium oxide (K2O) was at 1000 oCelcius (oC) with a content of  66.9%, while the lowest was at 700 oC with a content of  55.1%.  In contrast, the Si content in the form of SiO2 at a temperature of 1000 oC was very low.  The highest SiO2 content of K2SiO3 fertilizer at a temperature of 800oC was 35.1%.  The most optimal K2SiO3 fertilizer from this study was at a temperature of 800 oC with a content of 60.0% K2O and 35.1% SiO2. The incubation experiment  showed that the K2SiO3 with the rate of 2.50% was the most effective rate because it increased the exchangeable K, available Si, soil pH to relatively neutral and also reduced the exchangeable Al.